Biologika bei chronischer Rhinosinusitis - Pinggera, Leyla; Innerhofer, Veronika; Fischer, Natalie; Riechelmann, Herbert (Laryngo-Rhino-Otologie, 2020)
Chronic rhinosinusitis (CRS) is an inflammation of the nasal and paranasal mucosa, lasting for more than 12 weeks. By now approximately 15 % of the European and American population are affected, which indicates that CRS is a serious health problem. Beside other subgroups the most important classification is CRS with nasal polyps (CRSwNP) and without nasal polyps (CRSsNP). Standard-of-care therapies include nasal saline solution as well as topic or systemic corticosteroids. If this does not lead to a sufficient recovery, surgical therapy is a good option. A new therapy option is represented by biologics, particularly monoclonal antibodies (mAB). They are well-established for treatment of asthma bronchiale. Due to the fact that asthma is often associated with nasal polyps, and mAB may could also lead to improvements in CRS, studies were conducted. In the meantime there is a number of mAB which have emerged as an alternative treatment for patients with CRSwNP.
Keywords: chronische Rhinosinusitis; Therapie; Biologika; monoklonale Antikörper; Nasennebenhöhlenentzündung; Nasenpolypen